Preeclampsia Symptoms and Liver Function Tests in Women with Pre‐Eclampsia: Comparison with a Normal Pregnant Woman - Hamed, Salma; Ali, Marfoua (Scientific Journal for Faculty of Science-Sirte University, 2023)
Preeclampsia is a pregnancy-related condition that is linked to elevated blood pressure and proteinuria. It is one of the main causes of child and mother deaths in developed countries and only affects pregnant women during the second and third trimesters of pregnancy. Due to normal hepatic markers during pregnancy, our purpose is to examine these factors in pregnant women and their association with disorders such as preeclampsia. In this study, the liver function tests in pre-eclampsia and normal pregnancy were compared. This study included 100 pregnant women after 20 weeks of pregnancy, divided into two groups, Group A is the control group, which consisted of 40 pregnant women with normal blood pressure, and Group B is the preeclampsia group, which consisted of 60 preeclamptic women, whose blood pressure was greater than 140/90 mm Hg and whose proteinuria in a 24-hour period was greater than 300 mg. The Obstetrics and Gynecology Department of the Teaching Governmental Hospital in the northeastern Libyan city of El-Baida provided the samples. In both groups, we assessed the activity of the liver enzymes ALT, AST, and total bilirubin. According to the findings, there was no discernible difference between the two groups’ total bilirubin levels. The serum levels of ALT and AST across the two groups did, however, differ significantly (p 0.05). The results of this study indicate that preeclampsia-affected pregnant women had hepatic biomarkers that were higher than those of healthy pregnant women.